THE QUALITY OF PHYSIC NUT(Jatropha curcas L.) SEEDS PACKED IN PLASTIC MATERIAL DURING STORAGE - Rantje Lilly Worang; Okky Setyawati Dharmaputra; Rizal Syarief; Miftahuddin (BIOTROPIA, 2008)
The effect of storage duration on fungal population, moisture content, lipid and free fatty acid contents, lipase activity, viability and vigor of physic nut seeds was investigated. Physic nut seeds with initial moisture content of 7.9% were stored in plastic bags under warehouse conditions. Samples of physic nut were collected before storage, and subsequently after one to six months of storage. The results showed that the moisture contents increased after one month of storage, and became relatively constant up to six months of storage. The range of moisture contents (7.9 â€“ 8.4%) was safe for storage of physic nut seeds. Sixteen fungal species were isolated from physic nut seeds during six months of storage. Fungal population decreased with the increase of storage duration. At the beginning of storage, most of the fungi that infected the seeds were classified as field fungi, such as Colletotrichum sp., Cladosporium spp., and Fusarium spp.. Their populations decreased with the increase of storage duration. After three months of storage, the existence of field fungi was generally replaced by storage fungi, such as Aspergillus spp., and Penicillium spp. dominate the population. Lipid contents, viabilities and vigors decreased with the increase of storage duration, while free fatty acids and lipase activities increased. Under uncontrolled condiÂtions, physic nut seeds packed in plastic material can be stored up to one month for seeds to be planted, while it can be stored up to five months for producing oil.